COVID-19 pandemic through calls made to the call center (General Practice, 2022)
Introduction. From March 14th to May 04th, 2022, therehad been a call center in the Town Hall of Novog Sada (furthercall center). There were four general physicians (GPs)from Primary Healthcare Center “Novi Sad” on-call, and theygave information and answers to the questions asked by thecitizens about the COVID-19 pandemic.Objective. We aimed at presenting the structure of thequestions we asked on-call GPs in the call center.Method. Retrospective analysis of the phone calls, onone phone line, in one seven-hour shift, during 36 workingdays.Results and discussion: We analyzed 757 questions,classified into 14 call categories:1. Fever and health issues that might be connected to COVID-19,165 (21,80%).2. Health issues not connected to COVID-19, 134 (17,70%).3. Social problems that occurred after the going out ban for thoseover 65, and curfew, 68 (8,98%).4. Isolation measures, 67 (8,85%).5. Going to follow up health checks, 61 (8,06%).6. Problems buying food and drugs, 46 (6,08%).7. Going out ban, 44 (5,81%).8. Buying and using PPE and disinfectants, 20 (2,64% )9. Testing, 12 (1,59%).10. Going or rather not going to work, 11 (1,45%).11. Psychological problems, 9 (1,19%).12. Complaints of work organizations, 6 (0,79%).13. Questions that couldn`t be cataloged in any of the previouslymentioned categories, 89 (11,76%).14. Calls from other counties, 25 (3,30%), which was interesting.Conclusion: In the early phase of the pandemic oncallGPs helped citizens solve different problems, even nonhealthones. They remained the first line of contact with thehealth system, showing that primary health care, as a part ofthe health system, is always available.Keywords: COVID-19 pandemic, call center, organization,primary healthcare
Keywords: COVID-19 pandemic; call center; organization; primary healthcare